Multistage collapse of eight western Canary Island landslides in the last 1.5 Ma: Sedimentological and geochemical evidence from subunits in submarine flow deposits. (15th July 2013) - Hunt, J. E.; Wynn, R. B.; Talling, P. J.; Masson, D. G.
Abstract : [1] Volcaniclastic turbidites in the Madeira Abyssal Plain provide a record of major landslides from the Western Canary Islands in the last 1.5 Ma. These volcaniclastic turbidites are composed of multiple fining‐upward turbidite sands, known as subunits. The subunits indicate that the landslides responsible for the sediment gravity flows occurred in multiple stages. The subunits cannot result from flow reflection or splitting because the compositions of volcanic glasses from each individual subunit in an event bed are subtly different. This indicates that each subunit represents a discrete failure as part of a multistage landslide. This has significant implications for geohazard assessments, as multistage failures reduce the magnitude of the associated tsunami. The multistage failure mechanism reduces individual landslide volumes from up to 350 km 3 to less than 100 km 3 . Thus although multistage failure ultimately reduce the potential landslide and tsunami threat, the landslide events may still generate significant tsunamis close to source. Key Points: Multiple fining‐upwards sequences in deposits signify multistage landslides Subunits in El Golfo and Icod landslide deposits are correlated between basins Last eight flank collapses in the Canary Islands have been multistage failures